SPECIES OF FLIES LARVAE IN MICE (Mus musculus L.) WITH DISLOCATION, POISONED, AND BEHEADED TREATMENT IN BEDOYO, PONJONG, GUNUNGKIDUL - Ichsan Luqmana Indra Putra; Nuri Dwi Astuti (Universitas Negeri Medan, 2021)
Flies are insects that are often used in the field of forensic entomology as an indicator for determining the length of time of death (Post Mortem Interval). This study aims to determine the types and abundance of flies that come to the carcass of mice (Mus musculus L.) in several outdoor treatments. The research was conducted in an open area of 21 x 24 m in Bedoyo Village, Ponjong District, Gunung Kidul. There were 3 treatment groups, namely neck dislocation, poisoning and decapitation. Neck dislocation was performed by pulling the neck of the mice to death. Poisoned by using a sonde filled with 1 mL of liquid mosquito repellent and put into the digestive system of the mice. Beheading was done by cutting the neck of the mice. Place each carcass 2.5 meters apart. The collection of fly larvae was carried out every 2 days for 8 days. The fly larvae obtained were then identified up to the species level morphologically. The data obtained will be analyzed by inferential descriptive analysis. There are 3 species found on the carcass, namely Chrysomya megacephala, Chrysomya rufifacies, and Sarcophaga haemorrhoidalis. The highest abundance waslarvae with S. haemorrhoidalis 139 tails and the lowest C. rufifacies with 14 tails. The conclusion of this study is that each treatment given will bring fly larvae with different species and abundances.